Popular struggles for home in Goiânia-GO-Brazil:: narratives and spatialization from the Goiás press between 1975 and 1990 (Élisée - Revista de Geografia da UEG, 2021)
Brazil has a long history of urban planning policies. One of the most evident marks of these policies was the construction of three cities within the national territory. In Goiânia, built as the capital of the State of Goiás, the memory of the struggles for housing has much to contribute to the understanding of the quality, direction and socio-spatial effects of urban planning policies. Goiânia followed a historical trajectory of space production, encouraging geographic dispersion, hindering urban mobility and with strong repercussions on the socio-spatial periphery of housing. In this sense, our objective is to recompose the struggle for home based on the production of space and the role of popular movements. This reconstitution was methodologically carried out based on the literature review and the identification of the phenomenon through several reports published in the main newspapers in Goiânia, between 1970 and 1990, above all, the effects of popular struggles on the urban design of the municipality. There is also recognition of the links between popular struggles and the State, through the narratives described by the press covering the issue of home in Goiânia.
Keywords: popular struggles, home, Goiânia.